Immortal in death - Robb, J. D., 1950- (Robb, J. D., 1950- In death novel, 2022)
"She is one of the most sought-after women in the world. A top model who would stop at nothing to get what she wanted - even another woman's man. And now she's dead, the victim of a brutal murder. Police lieutenant Eve Dallas puts her life on the line to take the case when suspicion falls on her best friend, the other woman in the fatal love triangle. Eve finds that beneath the facade of glamour, the world of high fashion thrives on an all-consuming obsession with youth and fame. One that leads from the runway to the dark underworld of New York City, where drugs can be found to fulfill any desire--for a price"--